Experimental investigation of the seismic performance of flexible pipes for seismically isolated buildings. (1st November 2020) - Xie, Linlin; Yang, Cantian; Li, Aiqun; Lu, Jiaming; Zeng, Demin
Highlights: 27 metal flexible pipes and 24 rubber flexible pipes were tested. The schemes recommended by the code and used previously were compared. The effects of critical parameters on the seismic performance were investigated. The experimental data is accessible online for further investigation. Abstract: The seismic performance of flexible pipes significantly affects the resilience of seismically isolated buildings after an earthquake. However, the unqualified design or installation of flexible pipes is a critical issue in China and may also be observed in other countries due to the lack of corresponding design code. To investigate the performance of flexible pipes, 27 metal flexible pipes (MFPs) and 24 rubber flexible pipes (RFPs) with an expected deformation capacity of 400 mm were tested. The schemes recommended by the code and used previously in real engineering practices are compared comprehensively for two types of flexible pipes. The effects of critical parameters (i.e., the nominal inner diameter, installation length, and design length) on the damage evolution mode, deformation capacity, and failure mode are investigated. The test results indicate that 1) for previous MFPs designed with an installation length, two damage states are experienced, and the rupture of the outer net results in failure before 400 mm. However, water leakage is not observed owing to the strong deformation capacity of the inner bellows. 2) The cap of seismic performance of the previous MFPs considering maximum manufacturing redundancy is identified. Such an MFP with the smallest diameter ruptured before 400 mm, while a pull-out with a maximum length of 4 mm of the outer net is observed for other MFPs, and the function is generally well. 3) For previous RFPs, two damage states are experienced before 400 mm, but water leakage is observed along with rupture. A better deformation capacity is achieved for the RFP with a smaller diameter and longer design length. 4) Regarding the MFP and RFP designed according to the code, they can completely perform well under 30 cycles of 400 mm and function well after an earthquake. The research outcome can provide an important reference for the vulnerability research and seismic design of flexible pipes in seismically isolated buildings.